Reino de Deus e a Igreja: pressupostos da liturgia cristã - Octaviano, Guilherme Franco (2024)
Jesus' public ministry, centered on the inauguration and living of the Kingdom of God, laid the foundations for the entire ecclesiastical mission, including the liturgy. From the actions of Jesus of Nazareth, the assumptions of the Church's liturgy can be seen to be present, especially in the relational and communal character, typical of the dynamics of the reality of the Kingdom of God. In his parables, the Kingdom is announced, which is already present in everyday life and points to its transcendence. All of this is absorbed by the Church in its celebrations, which highlight the presence of the paschal mystery of Christ and prefigure the heavenly banquet. The Church, after the death, resurrection and glorification of the Lord, continues its mission, both to live the values of the Kingdom and to worship God, always configuring itself through the lex orandi and lex credendi. The Second Vatican Council represented a great milestone in the history of the Church, by rescuing not only ecclesial conscience, but also a liturgy more faithful to the Gospel and the mission of Jesus. The conciliar constitutions on the Church and on the liturgy highlight the intimate relationship between the configuration of the Church and the way in which the mysteries of faith are celebrated. After analyzing these texts, sixty years after the opening of the Council, it is possible to understand how the liturgy is experienced, especially within Christian communities: what are the advances, what are the issues that need to be matured and what are the views that distort the core of the liturgical reform and ecclesiastical. In order for the concepts specific to the liturgy, such as participation, spirituality, catechesis and appreciation of the Word of God, to be truly utilized, broad liturgical training and a constant stance of centrality of the Kingdom of God, the horizon of the ecclesiastical mission, are necessary